THE CORRELATION BETWEEN NURSES KNOWLEDGE AND PHLEBITIS PREVENTION EFFORTS AT IDAMAN HOSPITAL, BANJARBARU CITY - Muhammad Fasya Aminullah; Herry Setiawan; Eka Santi; M. Hadarani; Lola Illona E.K (Nurse and Health: Jurnal Keperawatan, 2023)
Background: A hospital is a type of healthcare facility that provides a variety of services. During the course of the treatment, patients may experience an increase in severity due to infectious diseases, one of which is Healthcare Associated Infections (HAIs). Another common type of HAIs is phlebitis. Phlebitis is a common infection associated with healthcare. Phlebitis prevention initiatives are primarily dependent on the expertise of nurses, this knowledge is directly tied to the nurses' performance of their duties and the success or failure of those duties in preventing patients from contracting phlebitis. Objectives: The purpose of this study was to determine the correlation between nurse’s knowledge and phlebitis prevention efforts at Idaman Hospital, Banjarbaru City Methods: A cross-sectional, correlational design was adopted for this research. Probability sampling using stratified random sampling is used for the sampling. In all, 129 nurses made up the study's sample. Data was gathered using questionnaires on basic demographics of the nurse, nursing knowledge, and phlebitis prevention efforts by nurse. Results: The results of the study found that there is a correlation between knowledge and efforts to prevent phlebitis at Idaman Hospital, Banjarbaru City (p value=0.001; OR=3.77). Nurses who have good knowledge have the opportunity to make efforts to prevent phlebitis events optimally by 3.77 times compared to nurses who have poor knowledge. Conclusion: The better the nurse's understanding of the incidence of phlebitis, the more effective will be the nurses' efforts to avoid phlebitis at Idaman Hospital in Banjarbaru City